Okresy życia ludzkiego według Ojców Kościoła - Józef Naumowicz (Vox Patrum, 2011)
The patristic writers variously enumerated the ages of human life. Some counted ten, some seven, six, five or four. They took number symbolism or the opinions of ancient authors as their starting point, but in their formulation the ages of human life concern not just the physical, intellectual or moral development of man but, often, also his spiritual development. They defined stages in the development of faith or love that can be described in terms analogous to those used for defining man’s age. Moreover, the patristic authors did not usually conclude their enumeration with old age. Human life passes ultimately into the age of rest (the seventh age) or into eternity (the eighth age), which has no end. Irenaeus of Lyon used the concept of the ages of life in proving that Jesus lived about fifty years. There were, in his opinion, theological arguments for such a mature age. Christ became one of us in order to accomplish the redemption and He therefore had to know all the ages of normal human life: not just birth, childhood and youth, but also maturity and old age. But the chronological and exegetical arguments Irenaeus gives are rather stretched. The most profound description of the ages of man was given by Augustine. He makes an original parallel with the seven days of creation and the seven ages of the history of the chosen people.